A Case Study of the School Behavior of Abused Children with Behavior Modification Intervention - Mayo-Dosayla, Charity Mae; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
Child abuse has become prevalent in the society and has reached an alarming state. An experience of abuse creates a domino effect on a child’s learning and socialization in school, and consequently impacts their holistic development. Anchoring on B.F. Skinner’s Operant Conditioning Theory, this study investigates the undesirable school behaviour of abused children and formulates an intervention program for behaviour modification. This case study documented the school behaviour of three primary school children identified as psychologically, physically, and sexually abused by the local Department of Social Welfare and Development. These abused children were selected using purposive sampling. Data collection was conducted through pre, and post-observation using a validated research-made Student Behaviour Inventory, in-depth interview, triangulation, and validated Student Behaviour Intervention Program (SBIP) anchored on Cognitive Behavioural approaches. Data were analysed using recursive textual analysis using Lichtman’s framework: coding, categorizing, and conceptualizing. Results of the study revealed that abused children have opposition, refusal, and resistance to orders; sensitiveness; tendency towards social withdrawal, aloofness, and melancholy; feelings of inferiority; and non-compliance to school requirements. Administration of SBIP to abused children produced slight modification in their behaviour. This study implies a consideration of the SBIP and its administration to children who have experienced abuse as an intervention to modify their school behaviour.